TRANSPARENCY FINANCIAL INFORMATION OF ORGANISASI PENGELOLA ZAKAT (OPZ) IN SHARIA PERSPECTIVE - Suginam Suginam; Ahmad Qorib; Saparuddin Siregar (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to determine whether the transparency of financial information as an effort to build public trust in financial management at the Zakat Management Organization (OPZ) is in accordance with Sharia or not. To provide confidence in the public in financial management, disclosure of information is required to the public as a disclosure of the performance report of an institution or organization. Transparency is a disclosure in the form of financial performance reports that are submitted openly in detail, clearly, easily accessible and can be conveyed periodically. This research was conducted based on literature studies from various sources from previous studies. This research method uses a qualitative descriptive research method that will describe the subject under study. The results of this study can be concluded that the transparency of financial information in Organisasi Pengelola zakat (OPZ)is still not managed in a Sharia manner. Keywords:Transparansi, Financial Information, OPZ, Sharia Perspektive